2018
DOI: 10.1103/physrevd.97.023527
|View full text |Cite
|
Sign up to set email alerts
|

Preheating after multifield inflation with nonminimal couplings. II. Resonance structure

Abstract: This is the second in a series of papers on preheating in inflationary models comprised of multiple scalar fields coupled nonminimally to gravity. In this paper, we work in the rigid-spacetime approximation and consider field trajectories within the single-field attractor, which is a generic feature of these models. We construct the Floquet charts to find regions of parameter space in which particle production is efficient for both the adiabatic and isocurvature modes, and analyze the resonance structure using… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
102
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 64 publications
(106 citation statements)
references
References 173 publications
(292 reference statements)
4
102
0
Order By: Relevance
“…We have confirmed that the early growth of δφ and δχ fluctuations in our lattice simulations closely matches the behavior calculated via Floquet analysis in Ref. [18]. Beginning around 2.6 e-folds, nonlinear rescattering among the δχ fluctuations drives rapid growth of the δφ fluctuations for ξ φ = 10.…”
supporting
confidence: 89%
“…We have confirmed that the early growth of δφ and δχ fluctuations in our lattice simulations closely matches the behavior calculated via Floquet analysis in Ref. [18]. Beginning around 2.6 e-folds, nonlinear rescattering among the δχ fluctuations drives rapid growth of the δφ fluctuations for ξ φ = 10.…”
supporting
confidence: 89%
“…However, as discussed later in Ref. [58][59][60] and independently in Ref. [61], multi-field models of inflation with nonminimal couplings to gravity can exhibit more efficient preheating behavior than previously thought, due to the contribution of the field-space structure to the effective mass of the fluctuations.…”
Section: Introductionmentioning
confidence: 88%
“…Models in this class exhibit interesting phenomenology during and after inflation, e.g. [45][46][47][48]. 9 Considering an inflationary scenario that proceeds towards a final Minkowski minimum, one should distinguish two types of potentials.…”
Section: )mentioning
confidence: 99%